Optimasi Minuman Serbuk Instan Antiobesitas menggunakan Metode Response Surface Methodology (RSM) Berbasis Rosela (Hibiscus sabdariffa l) - Intan Utami; Intan Utami; Mardiah; Lia Amalia; Siti Aminah (Universitas Djuanda, 2023)
Instant rosella anti-obesity drink is a beverage product in powder form, easily soluble in water, has a short rehydration time, practical in serving. This study aims to obtain an instant rosella anti-obesity drink formulation consisting of roselle extract, mangosteen peel extract, lemon extract and EGCG. This research was optimized using the Response Surface Methodology (RSM) method with a central composite design. Analysis of the formulation includes analysis of anthocyanin levels, levels of vitamin C in each formulation treatment. Based on the results of optimization of the anthocyanin and vitamin C content of instant anti-obesity drinks using the RSM method, formula 10 was obtained containing 4.75 g roselle, 0.2 g lemon extract, 0.5 g mangosteen peel extract and 0.0625 EGCG. This formula obtained anthocyanin levels of 895.72 mg/L and vitamin C levels of 53.3 mg/L with a powder drink pH of 2.5